Seasonal fertility of billy goats - Ibraheem Kutty C (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1995)
Biweekly data on body weight, scrotal circumference, testicular length and diameter and weekly data on semen parameters as volume, colour, pH, consistency, density, sperm concentration, mass activity, initial motility, sperm abnormality, vitality, metabolism and resistance to hyperosmotic medium of seven billy goats were pertaining to four seasons arrived at on the basis of a simultaneously kept daily record of maximum-minimum temperature, humidity and day length. It was statistically analysed to find out that the differences between seasons were significant to be attributed to the environmental variables. Mean body weight, scrotal circumference and testicular length and diameter were 43.62 ± 1.11 kg, 25.08 ± 0.12 cm, 8.57 ± 0.07 cm and 5.32 ± 0.03 cm respectively. There was no significant difference between the seasons except in testicular diameter and they were found to maintain an inverse relationship with day length and humidity. Mean volume, pH, initial motility, sperm concentration, total number of sperm per ejaculate, live sperm per cent, abnormal sperm per cent, MBR time and R value were 0.75 ± 0.04 ml, 6.25 ± 0.02, 73.51 ± 0.98 per cent, 3600 ± 144 millions/ml, 2660.6 ± 133.96 millions, 83.44 ± 0.76, 4.33 ± 0.43, 277.1 ± 14.27 seconds and 84.75 ± 12.39 ml respectively. There was no significant difference between seasons in these parameters except, pH, initial motility, live sperm per cent and R value. They were found to have a significant difference between seasons and were found to maintain either direct or indirect relationship with humidity and day length. Semen on extension with milk antibiotic extender and on storage under refrigeration was found to fast deteriorate rendering it unusable in 24 h. Semen on the day of collection and extension, was used for artificial insemination and result of insemination was found to be independent of the significant or nonsignificant seasonal differences of semen parameters. But, during the period of study, there were two peaks in conception and two peaks in birth corresponding to it. The pattern appeared to be an adjustment of reproduction by the female to the varying food availability and climate with little involvement of the male.